Aspects of Political Campaign in Political Communication Partai Keadilan Sejahtera (PKS) At The 2019 Legislative Election - Tatik Rohmawati (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to determine aspects of the Prosperous Justice Party (PKS) political campaign in the 2019 Legislative general election. Political communication is one of the ongoing problems of the Prosperous Justice Party because it is still not optimally implementing forms of political communication to support the party with the community. The focus in this paper is on aspects of political campaigns in the political communication of the Prosperous Justice Party. This paper is the result of research using a descriptive qualitative approach. Data collection methods used include observation, interviews and documentation studies. The focus of the analysis of the results of the study shows that the political communication of the Prosperous Justice Party (PKS) seen from the aspect of political campaigns has not met the expectations of PKS. The conclusion of this study is that the political campaign carried out by the Prosperous Justice Party was interesting with its flashmob, but the party did not carry out a more attractive campaign for millennials even though in the 2019 legislative general election there were many millennials who were only able to cast their votes but because the campaign did not Embrace the millennials, it causes less political campaigns to be carried out. The results of this study are expected to be useful for the community, especially to understand the importance of political campaigns in political communication carried out by political parties, especially the Prosperous Justice Party